2019
DOI: 10.1142/s0192415x19500757
|View full text |Cite
|
Sign up to set email alerts
|

Puerariae Radix Prevents Anxiety and Cognitive Deficits in Mice Under Oligomeric Aβ-Induced Stress

Abstract: To evaluate the therapeutic effects of Chinese herbal medicine (CHM) for Alzheimer’s disease (AD), we evaluated five CHMs in oligomeric A[Formula: see text]-treated mouse primary hippocampal neuronal cultures. The aqueous extract from the root of Pueraria lobata (Puerariae Radix; PR) showed better neuroprotective effects than did the other four CHM aqueous extracts, including Gardenia jasminoides, Eleutherococcus senticosus, Rhodiola rosea, and Panax, in the primary culture treated with saline or oligomeric A[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“… 58 More interestingly, in oligomer Aβ‐induced stress mice, puerarin effectively mitigated anxiety and prevented cognitive deficits. 59 …”
Section: Puerarin Alleviates the Clinical Relevance Of Chronic Inflammationmentioning
confidence: 99%
“… 58 More interestingly, in oligomer Aβ‐induced stress mice, puerarin effectively mitigated anxiety and prevented cognitive deficits. 59 …”
Section: Puerarin Alleviates the Clinical Relevance Of Chronic Inflammationmentioning
confidence: 99%
“…To clarify the mechanism of Puerariae Radix for neuroprotective effects, Huang HJ et al designed C57BL/6J mice that received a direct infusion of soluble oligomeric A to evaluate the extract of Puerariae Radix alleviation of Aβ deposition in the rat hippocampus. Experimentally, it was observed that Puerariae Radix aqueous extract decreased Aβ deposition, tau protein phosphorylation, inflammation, and loss of noradrenergic and serotonergic neurons, while increasing synaptophysin-and insulin-degrading enzymes against the toxicity of oligomeric Aβ [54].…”
Section: Moas Of the Extractmentioning
confidence: 99%
“…Other polyphenols have also been shown to obtain promising results in preclinical models of AD. Among them: Epigallocatechin gallate (EGCG) (green tea) is an α-secretase activity inhibitor [78,79]; Ferulic acid, found in grains, fruits, and vegetables, has been tested alone [80] or in combination with EGCC [81]; Silibinin (herb milk thistle; Silybum marianum) [82]; Apigenin, found in vegetables, fruits, herbs and plant-based beverages [83,84]; Puerarin, a Chinese herbal medicine [85,86]. Nevertheless, to our knowledge, in spite of the therapeutic potential of these compounds, they have not been tested in human patients.…”
Section: Nutraceuticals As a Treatment Of Admentioning
confidence: 99%